Kampanye Penggunaan Masker pada Kegiatan PKKMB STIE Bima - Puji Muniarty; Wulandari Wulandari; M. Rimawan (Jurnal Nusantara Mengabdi, 2022)
Purpose: Organizing campaign activities on the importance of wearing masks aimed at preventing the spread of COVID-19. The mask campaign as a form of concrete action from the academic community in this case new students through the socialization of the mask movement was carried out with the agenda of providing information about the use of masks in the community. Research Methodology: Campaign activities for distributing masks to prevent Covid-19 by new students participating in the PKKMB School of Economics (STIE) Bima by sixteen groups spread over several points in Bima City through the stages, namely; initial preparation, campaign implementation and monitoring. Descriptive methods of carrying out preparations are sharing tasks, compiling activity plans, observing activity locations, designing posters that will be displayed at campaign implementation points and purchasing masks and hand sanitizers. Results: The implementation of the mask campaign stage was carried out by new students participating in PKKMB STIE Bima with real actions at several crowded points. monitoring by the PKKMB Supervisor regarding the feedback from the community and the number of masks distributed. The PKKMB committee evaluates the smooth implementation of activities according to the agenda. Limitations: In the implementation of activities, there is still a lack of synergy with other social care groups so that the implementation of the campaign has not been spread. Contribution: Through campaign socialization on the importance of wearing masks, it is hoped that the community will understand the importance of preventing Covid-19